CARPOPHILUS HEMIPTERUS (COLEOPTERA: NITIDULIDAE) COMO AGENTE POLINIZANTE DE CHIRIMOYO (ANNONA CHERIMOLIA MILL.) BAJO CONDICIONES CONTROLADAS - López, Eugenio; Uquillas, Carolina (Acta Entomológica Chilena, 2022)
Carpophilus hemipterus pollination capacity was evaluated through exclosure, for cherimoya trees at Quillota, V Región-Chile. Similar results were obtained with manual pollination or with a population of 34 insects. Fraction of well formed fruits was similar under manual or insect pollination